Pengaruh Harga, Lokasi Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Doorsmer 225 Tebing Tinggi - Batubara, Rizki Wulanita (Digital Business Progress, 2024)
This research aims to determine the effect of price, location and service quality on customer satisfaction at the 225 Doorsmer Motorcycle Wash in Tebing Tinggi City. This type of research is quantitative descriptive research. The research population includes consumers at Amanda Brownies Tebing Tinggi City Branch. The research sample consisted of 37 respondents. The sampling method uses the total sampling method. Research data uses primary data sources. Data was obtained from the results of distributing questionnaires to respondents. The data analysis method uses multiple linear regression analysis methods. The results of the analysis show that the first hypothesis is accepted, meaning the price variable influences the customer satisfaction variable, the second hypothesis is accepted, meaning the location variable influences the customer satisfaction variable, the third hypothesis is accepted, meaning the service quality variable influences the customer satisfaction variable, and the fourth hypothesis is accepted, meaning price, location and service quality influence simultaneously (simultaneously) on the customer satisfaction variable.